Information space as a factor of optimization of the future specialists’ self-education - Elena A. Mingazheva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The training of a specialist at a university is determined by the quality of the educational process, during which it is necessary to take into account the situation on the labor market. Successful training largely depends on the students self-education, which is difficult and limited in the context of a pandemic. The conditions of todays realities dictate the methods and forms of the process of self-education of students. During the pandemic, students practice self-education on a remote basis. We consider this form as a complex functional system with its own logic of development and relatively independent stages of learning via the Internet. Changes in various fields of activity are observed daily, which increases the requirements for the quality of education of a competitive individual; the idea of online education using electronic information platforms that serve as a means of self-education of students at the university is analyzed. The process of organizing the educational process in disciplines and tasks from the position of digitalization, through the introduction of modern digital technologies in the process of education of academic courses at the time of the pandemic in the country and the world, becomes significant. The conceptual apparatus considered in the paper: information space, educational space, self-education, competence, competence approach. It clarifies the need to teach the discipline in combination to acquire professional experience; the idea of revealing and enriching the inner potential of each person, his development and self-education throughout his life is substantiated; a detailed analysis of psychological and pedagogical literature is given. The results of a comprehensive study conducted at Chelyabinsk State University confirm the dependence of communicative competence on the students self-education during the pandemic.